MENINGKATKAN KETERAMPILAN SOSIAL ANAK MELALUI METODE PROYEK DENGAN MENGGUNAKAN MEDIA BERMAIN BALOK DI RA NABILA PURWODADI KECAMATAN SUNGGAL KAB. DELI SERDANG - Bahtiar Siregar (Jurnal At-Tabayyun, 2019)
various stimuli so that children can develop optimally. Early education in early childhood has an impact on life in the future. Early childhood education is a central and fundamental and strategic education to develop the potential of early childhood. Early childhood is a critical age in the stages of spiritual, motor, cognitive, language, and social emotional development. This study uses a qualitative research method with research steps: data reduction, which is a form of analysis that sharpens, classifies, directs and presents data, namely to find a meaning from the data that has been obtained, then systematically arranged, from the form of information Verification, as well as analyze so that drawing conclusions. Based on empirical research results it is proven that the project method using the media of playing with blocks can develop social skills that are carried out in RA Nabila Purwodadi Sunggal.